UJI ADAPTASI BEBERAPA VARIETAS KEDELAI DI LAHAN SALIN DENGAN TEKNOLOGI BUDIDAYA JENUH AIR - Danner Sagala; Eka Suzanna; Prihanani Prihanani; Julian Nero (University of Prof. Dr. Hazairin, SH, 2013)
The objectives of the research were to find a variety well adapt in saline land and to know effect of saturated soil culture on growth and production of soybean. The research was conducted in saline land Bengkulu City from April to October 2012. The experiment was arranged in split plot randomized design. The main plot was culture technology consisted of conventional and saturrated soil culture. The sub plot was soybean variety consisted of tanggamus, slamet, wilis, Anjasmoro, Seulawah, and Sibayak. The result showed that growth and production of all varieties on conventional technology were lower than saturated soil culture. The well adapt Variety was anjasmoro.